Young Jewish poets who fell as Soviet soldiers in the Second World War - Lapidus, Rina (Routledge studies in the history of Russia and Eastern Europe, 2014)
"This book deals with the work of fifteen young Jewish poets who were killed, died of wounds, or were executed in captivity while serving in the Red Army in the Second World War. All were young, all were poets, most were thoroughly assimilated into Soviet society whilst at the same time being rooted in Jewish culture and traditions. Their poetry, written in Russian, Yiddish, and Ukrainian, was coloured by their backgrounds, by the literary and cultural climate that prevailed in the Soviet Union, and was deeply concerned with their expectation of impending death at the hands of the Nazis. The book examines the poets' backgrounds, their lives, their poetry and their deaths. Like the experiences and poetry of the British First World War poets, the lives and poems of these young Jewish poets are extremely interesting and deeply moving"--Page i